Leukocyte Coping Capacity: An Integrative Parameter for Wildlife Welfare Within Conservation Interventions - Huber, Nikolaus; Marasco, Valeria; Painer, Johanna; Vetter, Sebastian G.; Göritz, Frank; Kaczensky, Petra; Walzer, Chris (Frontiers in Veterinary Science, 2019)
Wildlife management, conservation interventions and wildlife research programs often involve capture, manipulation and transport of wild animals. Widespread empirical evidence across various vertebrate taxa shows that handling wildlife generally induces a severe stress response resulting in increased stress levels. The inability of individuals to appropriately respond to rapidly changing environmental conditions during and after manipulations may have deleterious and long-lasting implications on animal welfare. Therefore, mitigating stress responses in the frame of conservation interventions is a key animal welfare factor. However, we have a poor understanding of the metrics to adequately assess and monitor the dynamic physiological changes that animals undergo when subjected to stressful procedures in wild or captive conditions. A growing number of studies provide good evidence for reciprocal interactions between immune processes and stress. Here, we review the existing literature on a relatively new technique - Leukocyte Coping Capacity (LCC), a proxy for stress quantifying oxygen radical production by leukocytes. We discuss the strength and weaknesses of this immunological approach to evaluate stress, the individual capacity to cope with stress and the resulting potential implications for animal welfare. Additionally we present new data on LCC in captive roe deer (Capreolus capreolus) under long-time anesthesia and free-ranging Asiatic wild asses (Kulan; Equus hemionus kulan) were LCC was used to assess stress levels in animals captured for a reintroduction project.